Coatability And Bonding Characteristics Of Asphalt Binders Modified With Alkylamines-Based And Polyalkylene Glycol-Based Bonding Promoters - Rodzey, Muhamad Zulfatah Izham Muhamad (Universiti Sains Malaysia, 2021)
Conventional asphalt binder is widely used in the production of asphaltic concrete mixture. The rheological weakness of conventional asphalt binder had developed the interest among researchers to modify conventional asphalt binder by using various kinds of additives. The function and mechanisms involved are relying on the type and composition of additives used. Bonding promoters is an additive in asphalt binder that has shown a significant effect in enhancing the rheological properties of asphalt binder. The bonding performance of the asphalt binder is well improved. Economically, this is the best modification to be done to increase the lifespan of the pavement. The aim of this study is to enhance the coatability and bonding characteristics of modified asphalt binders by using bonding promoters, namely Polyalkylene Glycol-based (PLG) and Alkylamines-based (ALM). Different percentages were used, which are 0.5% and 1.0% for both bonding promoters. The evaluation of modified asphalt binder performance was compared with the conventional asphalt binder. The laboratory study was divided into three phases. The first phase is to determine the physical properties of modified asphalt binder by conducting softening point test, penetration test, ductility test, and elastic recovery test. Then, followed by evaluation of coatability performance of modified asphalt binder using static water immersion test and boiling water test. The utilization of sodium carbonate solution was included to enhance the moisture damage condition. Lastly, the pull-out test and shear compression test were conducted to determine the asphalt-substrate bonding performance under severe moisture damage conditions. The results of physical properties showed that incorporation of bonding promoter reduces the penetration values which indicates the increment of the ability to stiffen the binder. However, the penetration grade of all modified binders is still within 60/70 range. In terms of softening point, the results show no significant effect when compared to conventional asphalt binder. Apart from that, the ductility index and elastic recovery values show increment with bonding promoter. In terms of coatability performance, the static water immersion test shows no significant result. Still, under the action of boiling sodium carbonate, the coatability index of all modified asphalt binder reduces as the condition are considered as the most moisture damage condition. However, the coatability index is slightly higher than the control sample, indicating that bonding promoters are still enhancing the coatability performance. Based on the asphalt-substrate bonding performance, both bonding promoters can increase tensile strength and resist shear stress.